Fabrication and properties of carbon/carbon-carbon foam composites. Issue 21 (November 2019) - Wang, Bin; Xu, Bugao; Li, Hejun
This paper was focused on the development of a new composite for high thermal insulation applications with carbon/carbon (C/C) composites, carbon foams and an interlayer of phenolic-based carbon. The microstructure, mechanical properties, fracture mechanism and thermal insulation performance of the composite was investigated. The experiment results showed that the bonding strength of the C/C-carbon foam composite was 4.31 MPa, and that the fracture occurred and propagated near the interface of the carbon foam and the phenolic-based carbon interlayer due to the relatively weak bonding. The shear load-displacement curves were characterized by alternated linear slopes and serrated plateaus before a final failure. he experiment revealed that the thermal conductivity of the C/C-carbon foam composite was 1.55 W·m −1 ċK −1 in 800℃, which was 95.8% lower than that of C/C composites, proving that the thermal insulation of the new foam composite was greatly enhanced by the carbon foam with its porous hollow microstructure.